TECHECOSYS- IoT-Based Agriculture with the Blockchain Initiative - M., Surya; Manohar, S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The objective of this work is to enhance Secure IoT initiated platform for Agriculture domain with the support of MIRACL architecture to implement security. The effective monitoring and agricultural management is carried out with IoT sensors. The sensors are integrated to evaluate environmental factors like soil, temperature and humidity to create techno eco system to create an architecture name TECHECOSYS that integrated block chain, IoT for agriculture ecosystem. The architecture proven to be secure as it deals with MIRACL secure platform that provide extensive cloud secure platform for agri data integrations.